Association between medication complexity and follow-up care attendance: insights from a retrospective multicenter cohort study across 1,223 Chinese hospitals - Ma, Xuedi; Wang, Yang; Chen, Yongwu; Lian, Yufei; Zhao, Xiaoyu; He, Xuan; Qiu, Yue; Han, Sheng; Liu, Lihong; Wang, Chen (Frontiers in Pharmacology, 2024)
Background: Patients with Chronic Obstructive Pulmonary Disease (COPD) frequently face substantial medication burdens. Follow-up care on medication management is critical in achieving disease control. This study aimed to analyze the complexity of COPD-specific medication and determine how it impacted patients' attendance on follow-up care.Methods: This multicenter study includes patients with COPD from 1,223 hospitals across 29 provinces in China from January 2021 to November 2022. The medication Regimen Complexity Index (MRCI) score was used to measure COPD-specific medication complexity. The association between medication complexity and follow-up care attendance was evaluated using the Cox Proportional Hazard Model.Results: Among 16,684 patients, only 2,306 (13.8%) returned for follow-up medication management. The median MRCI score was 8.0 (Interquartile Range [IQR], 5.0 to 14.0).20.3% of the patients had high complex medication regimen (MRCI score > 15.0). The analysis revealed that compared to those with less complex regimens, patients with more complex medication regimens were significantly less likely to attend the follow-up medication care, with a Hazard Ratio (HR) of 0.82 (95% Confidence Interval [CI], 0.74 to 0.91). Specifically, patients with more complex dosage forms were 51% less likely to attend the follow-up care (95% CI, 0.43 to 0.57). This pattern was especially marked among male patients, patients younger than 65 years, and those without comorbid conditions.Higher medication complexity was associated with a decreased likelihood of attending follow-up care. To promote care continuity in chronic disease management, individuals with complex medication regimens should be prioritized for enhanced education. Furthermore, pharmacists collaborating with respiratory physicians to deprescribe and simplifydeprescribing and simplifying dosage forms should be considered in the disease management process.*a Adjusted for age and sex.†b Adjusted for age, sex, body mass index, systolic blood pressure, heart rate, and COPD Assessment Test.